Outcomes of artery embolisation for cystic fibrosis patients with haemoptysis: a 20‐year experience at a major Australian tertiary centre. Issue 9 (19th September 2021) - Semasinghe Bandaralage, Sahan P.; Tay, George; Hay, Karen; Megram, Emma; Smith, Daniel; Gadowski, Tahlia; Wright, Eimear; France, Megan; Bell, Scott; Reid, David
Abstract: There are no published data on Australian adult cystic fibrosis (CF) patient outcomes post bronchial arterial embolisation (BAE). We report 20 years of experience of BAE at a major Australian tertiary adult CF centre, where 46 patients underwent 100 BAE during this period. Mortality rate was comparable to previous studies (4% per year) and most who died had repeat BAE requirements. A higher proportion (9 out of 45) of patients were transplanted compared to previous publications. Repeat BAE was common and significantly higher in patients already on tranexamic acid.